The 360˚ View: Contextualized Virtual Reality Tours as Innovative Teaching Tool in Ecology for Elementary School Students - Gestiada, Rubert James; Tisoy, Frank Joseph; Lasala, Nestor Jr (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study. This study aims to develop and validate Contextualized Virtual Reality Tours as instructional materials for teaching ecology concepts to elementary students, focusing on enhancing students' conceptual understanding of ecological relationships and environmental awareness in a local context. Methodology. The study employed a descriptive-developmental research design and used the ADDIE model to create Contextualized Virtual Reality Tours. Tools included a 64MP mobile camera for video production, AI-generated voice narration, and a 4-point Likert scale assessment for validation. Data analysis was performed with Microsoft Excel. Main Findings. The Virtual Reality Tours significantly improved students' conceptual understanding, moving their performance from low to mastery level. Expert evaluations indicated high validity across content, instructional, and technical quality, and students rated the tours as highly acceptable and effective in increasing their engagement and comprehension of ecology concepts. Novelty/Originality of this Study. This study introduces a localized, semi-immersive Virtual Reality Tour model for ecology education, making science concepts accessible to students without field trips. Integrating contextualized ecological elements addresses the gap in immersive science education tools for local environments, promoting relevant and cost-effective learning.